Improving Teacher Performance Through Academic Supervision Activities at Madrasah Ibtidaiyah Nurul Huda Krembangan Surabaya - Tri Marfiyanto; Dwi Ristina; Harsono, Harsono (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2023)
This study aims to find a model of madrasa principal academic supervision that improves teacher performance. The location of this research is at Madrasah Ibtidaiyah Nurul Huda Krembangan, Surabaya. There were four respondents to the research. Collecting research data using in-depth interview techniques, observation, and documentation. The research data was then analyzed using data reduction and triangulation techniques. The results of this study found: 1) Implementation of academic supervision by the head of Madrasah Ibtidaiyah Nurul Huda Krembangan Surabaya is carried out every year at the beginning of the new school year, then divided into two stages, namely the first semester and the second semester. The stages of implementation of academic supervision are divided into three, namely: a) planning of academic supervision; b) implementation of academic supervision; and c) evaluation and follow-up of the results of the implementation of academic supervision. 2) There are three approaches used by madrasa heads: a) a directive approach; b) a non-directive approach; and c) a collaborative approach. The supervision model used is the artistic supervision model. The application of academic supervision using these models and approaches has implications for improving the performance of teaching staff at Madrasah Ibtidaiyah Nurul Huda Krembangan Surabaya. Teachers became more diligent in preparing everything related to learning activities and became more disciplined in carrying out their duties at the madrasah. This study recommends further research on the academic and clinical supervision of all teachers at Madrasah Ibtidaiyah Nurul Huda Krembangan Surabaya.